Physical Exercise Intervention for Children Undergoing Cancer Treatment: A Scoping Review - Mardhiyah, Ai; Safitri, Dian Dinnar Eka; Maryam, Nenden; Rakhmawati, Windy; Hendrawati, Sri (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: This research aimed to explore articles regarding physical exercise for children undergoing cancer treatment. Method: The research method used is scoping review. The process of doing a scoping review involves several steps, including developing research questions, establishing criteria for inclusion, a comprehensive search strategy, literature screening and selection, organizing data, and compiling, summarizing, and presenting the findings. The inclusion criteria encompassed full-text papers, namely randomized controlled trials or quasi-experimental research, published in English during the past decade (2014–2023). Pubmed, CINAHL, Scopus, and Proquest are used as search engines and database searches. Selected articles were extracted into charting data, analyzed with descriptive approaches, and the results reported. Results: The results found 14 articles, which were then categorized into three physical exercise programs, such as integrated physical exercise, technology-based physical exercise, and multimodal exercise. Outcomes obtained are cardiorespiratory fitness, motor performance, cancer-related fatigue, and quality of life. Conclusion: The side effects of cancer treatment in children may be mitigated through the implementation of physical exercise programs. This scoping review can be a consideration for optimizing pediatric nursing services by adding physical exercise interventions to the rehabilitation protocol as a supportive treatment for children who are currently undergoing cancer treatment.